Lower limb kinesio taping for blood circulation control in powerlifting and track and field sport - Dyakova, E. Yu.; Radyuk, A. I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to test and analyze kinesio taping effects on the lower limb blood flows in powerlifting and track and field sports.